2009
DOI: 10.1359/jbmr.090317
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trabecular Microarchitecture in Whole-Vertebral Body Biomechanical Behavior

Abstract: The role of trabecular microarchitecture in whole-vertebral biomechanical behavior remains unclear, and its influence may be obscured by such factors as overall bone mass, bone geometry, and the presence of the cortical shell. To address this issue, 22 human T 9 vertebral bodies (11 female; 11 male; age range: 53-97 yr, 81.5 ± 9.6 yr) were scanned with mCT and analyzed for measures of trabecular microarchitecture, BMC, cross-sectional area, and cortical thickness. Sixteen of the vertebrae were biomechanically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
97
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 56 publications
10
97
0
1
Order By: Relevance
“…Bone strength depends on microarchitecture of cortical and trabecular bone. (12) In women with vertebral fractures, trabecular parameters were impaired in those with normal cortical bone, whereas cortex was thinner in those with normal trabecular bone. (13) Women with vertebral fractures had thinner cortex and poor trabecular connectivity, as assessed by histomorphome-ORIGINAL ARTICLE J JBMR try.…”
Section: Introductionmentioning
confidence: 97%
“…Bone strength depends on microarchitecture of cortical and trabecular bone. (12) In women with vertebral fractures, trabecular parameters were impaired in those with normal cortical bone, whereas cortex was thinner in those with normal trabecular bone. (13) Women with vertebral fractures had thinner cortex and poor trabecular connectivity, as assessed by histomorphome-ORIGINAL ARTICLE J JBMR try.…”
Section: Introductionmentioning
confidence: 97%
“…Experimental and computational studies using human vertebrae (Rockoff et al, 1969;McBroom et al, 1985;Yoganandan et al, 1988;Silva et al, 1997;Eswaran et al, 2006) have investigated the relative contributions of these two tissues to lumbar vertebral body strength in axial compression and found that the cortical shell carries up to 45% of compressive loads depending on the region (maximum load at middle third of craniocaudal length), indicating that the role of trabecular bone in vertebral body strength is primary (Silva et al, 1997;Eswaran et al, 2006;Fields et al, 2009). However, the cortical shell's contribution to strength may be greater if the associated trabecular bone is poorly organized (low anisotropy) (Silva et al, 1997) or if bending is the primary mode of loading (Fields et al, 2009). Although axial compression is likely to be the major mode of lumbar vertebral body loading across most species (Smit, 2002), bending loads will also occur.…”
Section: Introductionmentioning
confidence: 99%
“…Although axial compression is likely to be the major mode of lumbar vertebral body loading across most species (Smit, 2002), bending loads will also occur. In humans, it is in this latter condition that the cortical shell's contribution to load bearing (e.g., Fields et al, 2009) may increase. The variety of positional behaviors among strepsirhines and other primates provides an opportunity to better understand the integrated function and mechanics of trabecular and cortical bone in lumbar vertebral bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human vertebrae, for example, alignment of the trabeculae along the axis of the spine makes the bone nearly twice as strong when loaded along the superior-inferior axis as when loaded in either the AP or left-right direction [45,91]. Combined imaging and computational modeling advances allow cancellous bone architecture to be captured (see articles by Donnelly [35] and Burghardt et al [18] in this issue) and input into mechanics-based models that can be used to understand the effect of architecture on stiffness of whole bones such as the vertebral body, distal radius, or proximal femur [42,57,98,126]. These computational modeling approaches will be essential to identify trabecular failure mechanisms in whole bones [41], especially at clinically important sites.…”
Section: Intrinsic Influences On Whole Bone Mechanicsmentioning
confidence: 99%